Time living with food insecurity and socio-demographic factors: longitudinal analysis in a city in the semi-arid region of Northeast Brazil - Ana Beatriz Macêdo Venâncio dos Santos; Poliana de Araújo Palmeira; Angelo Giuseppe Roncalli da Costa Oliveira (Public Health Nutrition, 2024)
Abstract